Radon measurement techniques in building materials and water using Italian and Ecuadorian samples - Orbe Ordóñez, Jheny; Cipparrone, Gabriella; Capua, Marcella (Università della Calabria, 2020)
Several studies have widely shown that there is a strict correlation between radon exposure and potential health hazard to the population. The indoor radon concentration depends on the radon exhalation from soil and building materials and radon in the domestic water supply. Accurate knowledge of the exhalation rate of building materials and radon concentration in drinking water plays an important role in reducing the risk for the population. Detailed research is being carried out into the measurements of the ex- halation rate of building materials and numerous publications are available. However, analysis of published results shows that a standard measurement protocol would be necessary and is not yet available. As regards the assessment of radon gas content in source water, interna- tional protocols are available, however, the high dependence of measurements on numerous parameters, both environmental and instrumental, it still re- quires studies to choose the most suitable instrumentation and procedure in particular circumstances and in measurement campaigns. This thesis presents the results of studies aimed at contributing to the realization of a protocol for measuring the radon exhalation rate in building materials. In addition, it presents the results of measurements of radon in wa-ter intended for human consumption under di erent experimental conditions. Standard instruments have been used for this purpose, such as scintillation chambers, gamma spectrometry, electrets and a radon chamber built in our laboratories. The emphasis will be on the work carried out with the radon chamber built for the research on the exhalation rate and adapted by us, for the rst time, for radon gas concentration measurements in water. The results obtained with the radon chamber are in excellent agreement with those obtained with the commercial instrumentation but the measure-of the measurements in water on di erent environmental parameters. Of no less importance is the fact that the studies were conducted in paral- lel in Italy, in the physics department of the University of Calabria (UNICAL) and in the analogous laboratory of the physics department at the Escuela Su- perior Polit ecnica de Chimborazo (ESPOCH) in Riobamba, Ecuador, where a radon chamber twin to the Italian one was built. Samples of Italian tu were taken to the ESPOCH laboratoryfor a com- parison of the measurements of the exhalation rate. In both laboratories exactly the same protocol was used, but each was equipped with an inde- pendent radon chamber and di erent instrumentation. Despite the di erent experimental and environmental circumstances, the results obtained are in excellent agreement with what was observed at UNICAL and con rm the quality of our protocol. With our protocols were studied di erent samples: Italian and Ecuado- rian building materials, commonly used in the construction of houses and buildings and water samples collected from wells and springs of the Calabria region in Italy and the Chimborazo province in Ecuador. The results of the radon exhalation rate of the analyzed materials show a wide variability due to the di erent physical and chemical properties of the samples. The results range from the minimum detectable to 0.86 Bq kg􀀀1 h􀀀1 obtained with a sample of crushed Italian tu measured with the closed chamber technique. The results, obtained using di erent detectors and tech- niques, show a satisfactory agreement. The results of the measurements of the radon concentration in the Ital- ian and Ecuadorian spring waters collected, compared to the reference value, indicated in the European Directive EURATOM 51/2013 dedicated to water intended for human consumption, show values well below 100 Bq l􀀀1 except for a Calabrian source, San Giovanni in Fiore, with a concentration of 133 Bq l􀀀1 measured with the closed chamber technique. Protection from this important gas necessarily involves actions to pre- vent and inform the population, as also indicated by the recent Italian law 101/2020 implementing the EURATOM Directive 59/2013. To this end, the activities carried out with projects aimed at high school can, at the same time, bring young people closer to scienti c research and a possible future in research, but also improve the knowledge of the dangers associated with radon for these students and the surroundings in which they live. For this reason, the last chapter of this work brie y summarizes the activities of the INFN RadioLab project in which I have been able to participate in this three-year period and which has involved about 150 Calabrian and Ecuado- rian students. ments with the chamber will allow a wide research activity on the dependence
UNIVERSITA’ DELLA CALABRIA Dipartimento di Fisica Dottorato di Ricerca in Scienze e Tecnologie Fisiche, Chimiche e dei Materiali. Ciclo XXXII
Keywords: Radon measurement